Regulación de plantas genéticamente editadas y selección del gen SAMT para la edición de carica papaya buscando resistencia a meleira - Gaitán, Julia Bibiana Merchán (2024)
This paper addresses the regulation of one of the most modern technologies for the control of plant pathologies, the CRISPR (Clustered regularly interspaced short palindromic repeats) technique, which is based on the action of a Cas protein and an gRNA that together can target specific areas of the DNA to modify them, through a systematic review of the regulatory systems of different countries. The different approaches adopted by countries in the Latin American region to regulate CRISPR technology were analyzed, taking into account the opportunities it offers and the possible associated ethical and social risks. So far, Brazil has analyzed the case-by case evaluation process of genetically modified crops by the regulatory committee CTNBio for the use of new plant breeding technologies to determine whether it would be considered a GMO or conventional breeding. This analysis was carried out because there is great interest in using CRISPR technology to develop new plant cultivars, especially plants relevant to Brazilian fruit growing. The Carica papaya cultivar, is of particular interest because of limitations in its production, due to the plant's susceptibility to the virus complex that causes papaya meleira disease, is economically and biologically relevant, as viruses have been identified in plant latex, a fluid derived from laticifers, which occur in more than 20 plant families and on which there is a body of information that points to laticifers as plant response systems to viruses. For this reason, a detailed review was conducted on the role of laticiferans of different species, examining the ability of both pro- and antiviral latex to protect plants, as well as its potential to be used as a natural source of defense molecules against insect vectors and fungal infections. The potential use of CRISPR in response to control viruses affecting laticifers was also evaluated through a compilation of articles targeting gene editing with specific expression or related to laticifer biology, confirming that it is possible to modulate laticifer function using CRISPR. The relationship of the PMeV complex in the C. papaya L. plant was discussed and the importance of the cloning of the Salicylate O-methyltransferase gene in the defense against this viral complex are discussed, due to its presence in the plant defense mechanisms related to laticifers. Describing experimental advances in the development of a protocol to silence the salicylate O-methyltransferase gene of C. papaya by means of the Golden Gate Assembly, detailing the design of gRNA for the construction and multiplication of gene editing vectors, intermediate steps in the process of gene silencing of the SAMT gene for the control of meleira disease in papaya, resulting in optimal conditions for the use of CRISPR technology in C. papaya plants.